2010
DOI: 10.1007/s10453-010-9189-4
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an integrated approach to microbial environmental monitoring in cultural heritage: experience at the Correggio exhibition in Parma

Abstract: Microbial environmental monitoring represents one of the most useful methods to assess potential risks related to the integrity of cultural heritage and people's health. The monitoring plan described in the present work is based on standardized techniques for measuring microbial air and surface contamination. Air contamination is assessed through both active and passive samplings, measuring the concentration of microbes in air (in colony forming units per cubic metre, CFU/m 3 ) and the rate at which microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The passive method, applied through the technique of impactsedimentation on Petri dishes, allowed the achievement of information on the part of bioaerosols that can be deposited under gravity onto a surface. This provides indications of the levels of contamination in the environment and the depositing risk to artefacts maintained in the crypt (Pasquarella et al, 2011). The method of active sampling, which was carried out through the use of the Andersen instrument, allowed the measurement of the concentrations of particles in the air that can be deposited by sedimentation or other mechanisms, providing, in particular, quantitative data on the viable suspended microflora.…”
Section: Discussionmentioning
confidence: 99%
“…The passive method, applied through the technique of impactsedimentation on Petri dishes, allowed the achievement of information on the part of bioaerosols that can be deposited under gravity onto a surface. This provides indications of the levels of contamination in the environment and the depositing risk to artefacts maintained in the crypt (Pasquarella et al, 2011). The method of active sampling, which was carried out through the use of the Andersen instrument, allowed the measurement of the concentrations of particles in the air that can be deposited by sedimentation or other mechanisms, providing, in particular, quantitative data on the viable suspended microflora.…”
Section: Discussionmentioning
confidence: 99%
“…Indoor fungi not only exist in the form of spores in the air but also colonize various materials as mycelia. Museums are colonized by various microbes, and the detailed lists of these species vary according to the type and organization of the museum, the type of exhibit, the indoor microclimate, and the local environment [2,[28][29][30]. The most common colonizing fungal taxa are species of Penicillium, Cladosporium, Alternaria, Aspergillus, and Chaetomium.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the microorganisms identified in this study are biodeteriogens that cause spots-disease, such as Aspergillus and Pseudomonas , and produce organic acids in the environment 38 39 . The occurrence of fungi such as Alternaria and Aspergillus and bacteria such as Bacillus and Pseudomonas in the air at heritage sites has been reported repeatedly 19 40 . The present study also revealed that the microbial communities on the wall paintings did not differ from those in other caves in the Mogao Grottoes, and no unique genus with a vital contribution to the biodeterioration of wall paintings was identified.…”
Section: Discussionmentioning
confidence: 99%